Legal Aspects in Obstetric Anesthesia - Chattopadhyay, S; Rudra, A; Ray, M; Sengupta, S; Goswami, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Obstetric anesthesia is a particularly high-risk sub-specialty of anesthesia and may lead to serious morbidities and even mortality. Good doctor-patient relation from the time of admission till discharge is the most important factor to avert future litigations. Any procedure done or planned should be clearly documented. Documentation should start with a valid consent in the patient’s own language, and have all three components of voluntariness, capacity and knowledge. A ‘Surgical Safety’ checklist is particularly helpful in documentation and decreasing errors. Safety of the mother (and her child) is paramount. Both regional as well as general anesthesia, either inadvertently or if not administered properly may be associated with morbidities like headache, pain and emotional distress. However, deaths do occur and general anesthesia is associated with care should be routine practice and inculcated by everyone involved in patient care.